The Relationship Between The Level of Knowledge and Attitudes of Mothers Regarding The First 1000 Days Of Life With The Nutritional Status of Toddlers Aged 24-59 Months In Working Area of Puskesmas Anak Air Padang City in 2024 - Yenda, Viona; Ayudia, Fanny; Ririn, Ririn; Erwani, Erwani (STIKes Alifah Padang, 2024)
Toddler nutritional status is an important indicator of children's health, growth, and development. Based on UNICEF et al., (2023),6.8 percent of children under 5 years of age will be affected by wasting, of which 13.6 million (2.1 percent) suffer from severe wasting. The Indonesian Nutritional Status Survey (2022) reported that the prevalence of wasting in Indonesia is currently 7.7%, where this case has increased from the previous year with a prevalence of 7.1% in 2021. The study aims to determine the Relationship between the Level of Knowledge and Attitudes of Mother about the First 1000 Days of Life with the Nutritional Status of Toddlers Aged 24-59 Months in the Work Area of Puskesmas Anak Air Padang City in 2024. The research method used is quantitative with a cross-sectional design. Data collection was carried out from June 10 to July 8. The population of the study was all mothers who had toddlers aged 24-59 months in the working area of Puskesmas Anak Air, totaling 658 people. Sampling used the Simple random sampling method with a lottery technique totaling 86 people. Data collection used a questionnaire. Data analysis used univariate and bivariate with the Chi Square statistical test. The results showed that 9.3% of mothers had low knowledge and 27.9% had negative attitudes about 1000 HPK. Of the respondents, 3.5% had toddlers with poor nutritional status. Statistical tests showed a significant relationship between the level of knowledge about 1000 HPK and the nutritional status of toddlers (p = 0.022), but there was no significant relationship between attitudes and the nutritional status of toddlers (p = 0.465). In conclusion, mothers with low knowledge tend to have toddlers with malnutrition. It is recommended that Puskesmas Anak Air provide counseling regarding the assessment and fulfillment of balanced nutrition according to toddler needs.